The Influence of Mental Resilience on the Positive Coping Style of Air Force Soldiers: A Moderation- Mediation Model - Zhao, Xiaojun; Wang, Ju; Shi, Changxiu (Frontiers in Psychology, 2020)
In this study, 697 air force soldiers from China were investigated with the Chinese Resilience Scale, Military Emotional Regulation Scale, Simple Coping Scale and Social Support Rating Scale. Structural equation modeling revealed the following: (1) resilience had a positive predictive effect on active coping style; (2) the emotion regulation strategy of self-comfort mediated the relationship between resilience and positive coping style; and (3) social support moderated the latter half of the intermediary process, in which resilience influenced the active coping style of soldiers through self-comfort. The influence of resilience on air force soldiers was a mediating effect, in which resilience could not only directly predict the coping style of soldiers but could also influence their coping style through self-comfort. Social support enhanced the influence of self-comfort on coping style. The study has great theoretical and empirical value for promoting the mental health of soldiers and using positive coping strategies.